2021
DOI: 10.1002/prca.202000094
|View full text |Cite
|
Sign up to set email alerts
|

Primary angle closure glaucoma is characterized by altered extracellular matrix homeostasis in the iris

Abstract: Purpose To characterize the proteome of the iris in primary angle closure glaucoma (PACG). Experimental Design In this cross‐sectional study, iris samples were obtained from surgical iridectomy of 48 adults with PACG and five normal controls. Peptides from iris were analysed using liquid chromatography‐tandem mass spectrometry on an Orbitrap Q Exactive Plus mass spectrometer. Verification of proteins of interest was conducted using selected reaction monitoring on a triple quadrupole mass spectrometer. The main… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 85 publications
0
4
0
Order By: Relevance
“…The use of “omics” for disease pathogenesis or staging is not new and has been studied in several groups ( Wang-Su et al, 2003 ; Bai et al, 2020 ; Rao et al, 2021 ; Semba et al, 2021 ). Multiomics studies will enable significant progress in the understanding of disease at multiple levels in the coming years, which are as follows: i) identification of biomarkers to be used in the diagnosis or prognosis of the disease, ii) advancement in the knowledge of possible physiopathological mechanisms, and iii) development of new and effective therapeutic strategies.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The use of “omics” for disease pathogenesis or staging is not new and has been studied in several groups ( Wang-Su et al, 2003 ; Bai et al, 2020 ; Rao et al, 2021 ; Semba et al, 2021 ). Multiomics studies will enable significant progress in the understanding of disease at multiple levels in the coming years, which are as follows: i) identification of biomarkers to be used in the diagnosis or prognosis of the disease, ii) advancement in the knowledge of possible physiopathological mechanisms, and iii) development of new and effective therapeutic strategies.…”
Section: Introductionmentioning
confidence: 99%
“…Wang-Su et al reported an abundance of αA-, αB-, and βB2-crystallins in both freshly isolated and cultured human lens epithelial (HLE) cells ( Wang-Su et al, 2003 ). Semba et al concluded that the ECM composition and homeostasis are altered in the iris in primary closed-angle glaucoma (PACG) through a high-throughput proteomics approach ( Semba et al, 2021 ). The practice of multiomics research in the ocular tissues of neurological disorders and other pathological conditions has gained momentum with advanced technological techniques ( Wang-Su et al, 2003 ; Vogeser and Seger, 2008 ; Sethi and Zaia, 2017 ; Bai et al, 2020 ; Semba et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the high-resolution Orbitrap data, the sequentially stepped targeted MS/MS (sst-MS/MS) method was developed for targeted peptide analysis. After acquiring global comparative proteomics data using Q-Exactive Plus mass spectrometer, 32 changed proteins were validated using the SRM of selected peptides that were unique to those proteins [34]. Similarly, Gu et al used globally optimized targeted MS for metabolomics that combined the advantages of targeted detection and untargeted profiling with an LC−triple quadrupole MS [35].…”
Section: Design Of Srm Transitions From the Mzvault Librarymentioning
confidence: 99%
“…So what role might these functions of the NTD of TSP-1 play in the pathologic changes to ocular tissue structure in glaucoma? Multiple studies suggest that TSP-1 expression is variably increased in the glaucomatous TM and in the (LC of the optic nerve head and sclera at the posterior of the eye (Tripathi et al, 1991;Hiscott et al, 1996;Flugel-Koch et al, 2004;Rhee et al, 2009;Chatterjee et al, 2014;Semba et al, 2021). Furthermore, knockout of the Thbs1 gene in mice reduces intra-ocular pressure (Haddadin et al, 2012).…”
Section: Relevance To Glaucomamentioning
confidence: 99%